Frontispiece: Biocatalytic Strategies towards [4+2] Cycloadditions. Issue 28 (17th May 2019) - Lichman, Benjamin R.; O'Connor, Sarah E.; Kries, Hajo
Abstract : Biocatalysis and synthetic organic chemistry play by the same physicochemical rules, but their strong suits are fundamentally different. A case in point are cycloaddition reactions: their wide use in synthetic organic chemistry contrasts with their scarcity in biological systems. In their Minireview onpage 6864 ff., H. Kries et al. discuss and describe the biocatalytic strategies employed by natural [4+2] cyclases and designer enzymes created in the lab. These enzymes can potentially be developed into biocatalytic tools for organic synthesis in the future.